1986
DOI: 10.1007/bf01314286
|View full text |Cite
|
Sign up to set email alerts
|

Studies on epidemiology and pathogenicity of porcine circovirus

Abstract: Antibodies to porcine circovirus (PCV) which is the smallest animal virus known so far were found in 77-95 per cent of sera from slaughter pigs gathered in Berlin and two districts of Northern Germany. About 60 per cent of these positive sera had relatively high titres similar to those in experimentally infected pigs 3-6 weeks after infection. This indicates that the animals might have become infected during the fattening period. Sera from 2-3 year old pigs from a laboratory animal breeding institution were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
265
2
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(288 citation statements)
references
References 1 publication
6
265
2
8
Order By: Relevance
“…Porcine circovirus type 1 (PCV1) serological studies in non-porcine species have also led to controversial results. Tischer et al [21] detected antibodies to PCV1 in human beings, cattle and mice, while other workers did not find any evidence of PCV1 infection in other species (sheep, cattle, turkeys, chickens, human beings, mice, rabbits, goats and ducks) but swine [1]; PCV1 has also been demonstrated as non-pathogenic for swine [2,20]. However, at present, no association has been established between infection of both porcine circoviruses and non-porcine species.…”
Section: Introductionmentioning
confidence: 91%
“…Porcine circovirus type 1 (PCV1) serological studies in non-porcine species have also led to controversial results. Tischer et al [21] detected antibodies to PCV1 in human beings, cattle and mice, while other workers did not find any evidence of PCV1 infection in other species (sheep, cattle, turkeys, chickens, human beings, mice, rabbits, goats and ducks) but swine [1]; PCV1 has also been demonstrated as non-pathogenic for swine [2,20]. However, at present, no association has been established between infection of both porcine circoviruses and non-porcine species.…”
Section: Introductionmentioning
confidence: 91%
“…9,14,23 Those studies documented a high prevalence of seroconversion to PCV 1 in healthy pigs. Those data, together with experimental infections with PCV 1, suggested that infection by PCV 1 was endemic and apparently nonpathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…6,13,24 Although it has been documented in vitro that the replication of at least the original isolates of PCV are dependent on the S, or synthesis phase, of the cell cycle, currently little is known about the requirements for PCV growth in vivo. 23 Replication of both PPV and PCV depends on cellular enzymes expressed during S phase of the cell cycle, 24 suggesting that PPV and PCV may target the same cells in vivo. They may interact in some way to synergistically enhance replication, or the same physiologic factors may enhance replication of both viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The PCV was first isolated in 1974 as a contaminant of the porcine kidney cell line PK-15. 16,18 Antibodies to the PCV strain isolated from the PK15 cell line (PCV PK-15) are widespread in swine populations, 4,15,17 but this strain is not associated with either clinical illness or pathological changes in pigs. 1,17 Antibodies to PCV PK-15 have been detected in humans, 14 but the significance of this finding is not known.…”
mentioning
confidence: 99%